Математичні моделі оптимізації для обґрунтування та знаходження ваг об’єктів по неоднорідних матрицях парних порівнянь - Pavlov, A. A.; Kut, V. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
Constructive mathematical models of optimization for finding of weights in the Analytic Hierarchy Process by T. Saaty are formulated and substantiated using the matrix of pair comparisons which has inhomogeneous information of the expert about pair comparisons of objects.